KATABEL Flashcards for Fable-Based Dance Learning in Primary School - Marcella Nadya Irafany; Deasylina da Ary (WISE Pendidikan Indonesia, 2026)
Dance instruction in primary school requires learning media that make movement concepts concrete, engaging, and usable for young learners. This study developed KATABEL, a fable-based dance flashcard medium, and examined its feasibility and preliminary effectiveness in Grade 4 dance learning. The study employed research and development using the ADDIE framework and involved 29 students at a public primary school in Pati Regency, Indonesia. KATABEL combines animal-fable narratives, illustrations, QR-code-linked movement videos, and prompts for imitating, adapting, sequencing, and presenting movement. Feasibility was assessed by content and media experts; implementation evidence was obtained through sequential small-group (n = 6) and large-group (n = 23) pretest-posttest trials. Content and media validation yielded 93% and 96%, respectively, placing the product in the highly feasible category. Shapiro-Wilk results supported normality, and paired-sample tests indicated significant gains in both trials (small group: t = -8.174, p < .001; large group: t = -18.325, p < .001). Mean normalized gains were 0.6879 and 0.7366. KATABEL offers a low-cost, human-centered physical-digital learning resource that supports movement exploration, participation, and equitable access to primary arts learning.